The genetic footprint of the European Roma diaspora: evidence from the Balkans to the Iberian Peninsula - Giacomo Francesco Ena; Aaron Giménez; Annabel Carballo-Mesa; Petra Lišková; Marcos Araújo Castro e Silva; David Comas (Human Genetics, 2025)
The Roma people have a complex demographic history shaped by their recent dispersal from a South Asian origin into Europe, accompanied by continuous population bottlenecks and gene flow. After settling in the Balkans around 1,000 years ago, the Roma gradually dispersed across Europe, and approximately 500 years ago, they established in the Iberian Peninsula what is now one of the largest Roma populations in Western Europe. Focusing specifically on the Iberian Roma, we conducted the most comprehensive genome-wide analysis of European Roma populations to date. Using allele frequency and haplotype-based methods, we analysed 181 individuals to investigate their genetic diversity, social dynamics, and migration histories at both continental and local scales. Our findings demonstrate significant gene flow from populations encountered during the Roma’s dispersal and confirm their South Asian origins. We show that, between the 14th and 19th centuries, the Roma spread westward from the Balkans in various waves, with multiple admixture events. Furthermore, our findings refute previous hypotheses of a North African dispersal route into Iberia and genetic connections to Jewish populations. The Iberian Roma exhibit ten times greater genetic differentiation compared to non-Roma Iberians, indicating significant regional substructure. Additionally, we provide the first genetic evidence of assortative mating within Roma groups, highlighting distinct mating patterns and suggesting a gradual shift towards increased integration with non-Roma individuals. This study significantly enhances our understanding of how demographic history and complex genetic structure have shaped the genetic diversity of Roma populations, while also highlighting the influence of their evolving social dynamics.

GLOSSAQUA : A global dataset of size spectra across aquatic ecosystems - Zeynep Ersoy; Charlotte Evangelista; Aitor Larrañaga; Daniel M. Perkins; Javier Sánchez‐Hernández; Teofana Chonova; David Cunillera‐Montcusí; Carmen García‐Comas; Jorge García‐Girón; Ioar de Guzman; Justin Pomeranz; Victor Saito; et al. (Ecology, 2025)
Body size is a key trait in ecology due to its influence on metabolism and many other life‐history traits that affect population and community responses to environmental variation as well as ecosystem properties. The size spectrum represents the relationship between abundance (or biomass) and body size, independent of species identity. Size spectrum parameters, such as the slope or intercept, have been applied extensively as indicators of ecological status across multiple ecosystem types. The GLOSSAQUA dataset includes data from mainly heterotrophic communities composed of single (e.g., zooplankton, macroinvertebrates, or fish) to multiple taxonomic groups (e.g., from primary consumers to apex predators, and phytoplankton to large zooplankton), across diverse spatial and temporal scales, from surveys in freshwater (43% studies), marine (52% studies) and brackish (5% studies) ecosystems. In total, we compiled a unique global dataset of 8459 size spectrum slopes or exponents, 5237 intercepts, and 4,497 linearity coefficients (i.e., defined by the R 2 of the linear fit of the size spectrum) from 127 articles and gray literature (i.e., unpublished datasets). The current dataset aims to help identify the main drivers shaping aquatic size spectrum parameters at a global scale and contribute to cross‐ecosystem comparisons. GLOSSAQUA can serve to explore questions such as factors influencing spatial and temporal dynamics of community size structure, comparing the response of community size structure between natural versus human‐impacted sites, and comparing global patterns in different aquatic ecosystems. We encourage researchers, especially those from underrepresented geographical areas (e.g., South Hemisphere and Asia) to fuel this dataset in the future. The dataset is provided under a CC‐BY‐NC‐S4 4.0 license, and users are encouraged to cite this data paper when using the data.

Improvement of the safety of artisanal Spanish fermented sausages: Spotlight on the role of bacteriocinogenic Lactiplantibacillus paraplantarum against a Companilactobacillus alimentarius histaminogenic strain - Federica Barbieri; Giulia Tabanelli; Oriol Comas-Basté; Mariluz Latorre-Moratalla; Chiara Angelucci; Fausto Gardini; Chiara Montanari; J. David García-López; Alberto Baños (Food Control, 2025)

Electro-responsive hyaluronic acid-based click-hydrogels for wound healing - Víctor Castrejón-Comas; Nil Mataró; Leonor Resina; David Zanuy; Quim Nuñez-Aulina; Joel Sánchez-Morán; Hamidreza Enshaei; Marc Arnau; Helena Muñoz-Galán; Joshua C. Worch; Andrew P. Dove; Carlos Alemán; et al. (Carbohydrate Polymers, 2025)

Enhancing reclaimed water distribution network resilience with cost-effective meshing - David Martínez; Sergi Bergillos; Lluís Corominas; Joaquim Comas; Fenghua Wang; Robert Kooij; Eusebi Calle (Science of The Total Environment, 2024)

Population history modulates the fitness effects of Copy Number Variation in the Roma - Marco Antinucci; David Comas; Francesc Calafell (Human Genetics, 2023)
We provide the first whole genome Copy Number Variant (CNV) study addressing Roma, along with reference populations from South Asia, the Middle East and Europe. Using CNV calling software for short-read sequence data, we identified 3171 deletions and 489 duplications. Taking into account the known population history of the Roma, as inferred from whole genome nucleotide variation, we could discern how this history has shaped CNV variation. As expected, patterns of deletion variation, but not duplication, in the Roma followed those obtained from single nucleotide polymorphisms (SNPs). Reduced effective population size resulting in slightly relaxed natural selection may explain our observation of an increase in intronic (but not exonic) deletions within Loss of Function (LoF)-intolerant genes. Over-representation analysis for LoF-intolerant gene sets hosting intronic deletions highlights a substantial accumulation of shared biological processes in Roma, intriguingly related to signaling, nervous system and development features, which may be related to the known profile of private disease in the population. Finally, we show the link between deletions and known trait-related SNPs reported in the genome-wide association study (GWAS) catalog, which exhibited even frequency distributions among the studied populations. This suggests that, in general human populations, the strong association between deletions and SNPs associated to biomedical conditions and traits could be widespread across continental populations, reflecting a common background of potentially disease/trait-related CNVs.

The genomic analysis of current-day North African populations reveals the existence of trans-Saharan migrations with different origins and dates - Marcel Lucas-Sánchez; Karima Fadhlaoui-Zid; David Comas (Human Genetics, 2023)
The Sahara Desert has acted as a barrier to human gene-flow between the northern and central parts of Africa since its aridification. Nonetheless, some contacts between both sides of the desert have occurred throughout history, mainly driven by commercial activity. Part of this was the infamous trans-Saharan slave trade, which forcedly brought peoples from south of the Sahara to North Africa from Roman times until the nineteenth century. Although historical records exist, the genetic aspects of these trans-Saharan migrations have not been deeply studied. In the present study, we assess the genetic influence of trans-Saharan migrations in current-day North Africa and characterize its amount, geographical origin, and dates. We confirm the heterogeneous and generally low-frequency presence of genomic segments of sub-Saharan origin in present-day North Africans acquired in recent historical times, and we show evidence of at least two admixture events: one dated around the thirteenth–fourteenth centuries CE between North Africans and a Western-sub-Saharan-like source similar to current-day Senegambian populations, and another one dated around the seventeenth century CE involving Tunisians and an Eastern-sub-Saharan-like source related to current-day south-Sudan and Kenyan populations. Time and location coincide with the peak of trans-Saharan slave-trade activity between Western African empires and North African powers, and are also concordant with the possibility of continuous recent south-to-north gene-flow. These findings confirm the trans-Saharan human genetic contacts, providing new and precise evidence about its possible dates and geographical origins, which are pivotal to understanding the genomic composition of an underrepresented region such as North Africa.

The place of metropolitan France in the European genomic landscape - Simone Andrea Biagini; Eva Ramos-Luis; David Comas; Francesc Calafell (Human Genetics, 2020)

Lymnaeid Snail Vectors of Fascioliasis, Including the First Finding of Lymnaea neotropica in Ecuador, Assessed by Ribosomal DNA Sequencing in the Southern Zone Close to the Peru Border - A. F. Villavicencio; M. Dolores Bargues; Patricio Artigas; R. Guamán; S. M. Ulloa; J. Romero; David Osca; Santiago Mas-Coma (Acta Parasitologica, 2019)

Challenges in assessing the real incidence of chronic lymphocytic leukemia: 16 years of epidemiological data from the province of Girona, Spain - Marta Solans; Gemma Osca-Gelis; Raquel Comas; Josep Maria Roncero; David Gallardo; Rafael Marcos-Gragera; Marc Saez (Cancer Causes & Control, 2018)

Adaptive evolution of loci covarying with the human African Pygmy phenotype - Isabel Mendizabal; Urko M. Marigorta; Oscar Lao; David Comas (Human Genetics, 2012)

Recombination networks as genetic markers in a human variation study of the Old World - Asif Javed; Marta Melé; Marc Pybus; Pierre Zalloua; Marc Haber; David Comas; Mihai G. Netea; Oleg Balanovsky; Elena Balanovska; Li Jin; Yajun Yang; GaneshPrasad ArunKumar; et al. (Human Genetics, 2012)

Linguistic and maternal genetic diversity are not correlated in Native Mexicans - Karla Sandoval; Leonor Buentello-Malo; Rosenda Peñaloza-Espinosa; Heriberto Avelino; Antonio Salas; Francesc Calafell; David Comas (Human Genetics, 2009)

Extreme individual marker FST values do not imply population-specific selection in humans: the NRG1 example - Michelle Gardner; Scott Williamson; Ferran Casals; Elena Bosch; Arcadi Navarro; Francesc Calafell; Jaume Bertranpetit; David Comas (Human Genetics, 2007)

Insights into the western Bantu dispersal: mtDNA lineage analysis in Angola - Stphanie Plaza; Antonio Salas; Francesc Calafell; Francisco Corte-Real; Jaume Bertranpetit; ngel Carracedo; David Comas (Human Genetics, 2004)

Comparative Analysis of Alu Insertion Sequences in the APP 5′ FlankingRegion in Humans and Other Primates - Jordi Clarimón; Aida M. Andrés; Jaume Bertranpetit; David Comas (Journal of Molecular Evolution, 2004)

Alu insertion polymorphisms in NW Africa and the Iberian Peninsula: evidence for a strong genetic boundary through the Gibraltar Straits - David Comas; Francesc Calafell; Noufissa Benchemsi; Ahmed Helal; Gerard Lefranc; Mark Stoneking; Mark A. Batzer; Jaume Bertranpetit; Antti Sajantila (Human Genetics, 2000)